2021
DOI: 10.1017/ice.2021.493
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical complications of central venous catheters in children: A cohort study

Abstract: Background: Despite the numerous advantages of central venous catheters (CVCs), they have been associated with a variety of complications. Surveillance for mechanical complications of CVCs is not routine, so the true incidence and impact of this adverse patient outcome remains unclear. Setting and methods: Prospectively collected CVC data on mechanical complications were reviewed from a centralized database for all in-hospital patient days at our tertiary-care hospital from January 2001 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 25 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…Other investigators have explored nonelective CVC removal; however, the incidence and risk factors have received little attention. 7,8,[21][22][23][24][25] In this study, the most common CLANC types were malfunction, malposition, breakage, and dislodgement. Understanding the types of events and populations where catheter loss occurs may inform CVC selection and quality improvement initiatives.…”
Section: Discussionmentioning
confidence: 71%
“…Other investigators have explored nonelective CVC removal; however, the incidence and risk factors have received little attention. 7,8,[21][22][23][24][25] In this study, the most common CLANC types were malfunction, malposition, breakage, and dislodgement. Understanding the types of events and populations where catheter loss occurs may inform CVC selection and quality improvement initiatives.…”
Section: Discussionmentioning
confidence: 71%
“…In the literature, there are no studies available that analyzed the vascular access performance of the entire acute care phase of pediatric trauma patients. The comparability of existing studies on pediatric vascular access is difficult due to considerably different settings, designs, sample sizes and groups of operators [ 6 , 8 , 9 , 12 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical complications and malposition had no relevant impact on the treatment course, supporting other studies in the pediatric population and adult trauma population of our study center, in which we found considerable malposition rates of almost 30% [ 47 , 48 ]. In the literature, common factors associated with mechanical complications in pediatric CVC placement are left-sided catheters, patient weight, sex, the team´s learning curve and the use of ultrasound [ 9 , 41 , 42 , 43 , 44 , 47 ]. The emergency placement of a CVC in pediatric patients requires considerable experience and training under nonemergency circumstances, and should not be performed by novices [ 11 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 In previous research, PICCs were the most commonly used CVAD in our setting, representing 48%-54% of inserted CVADs, and mechanical complications were common. 9,12 In this study, we sought to identify characteristics of patients and PICC device that were associated with mechanical complications to inform efforts and interventions to reduce the failure of PICC devices.…”
mentioning
confidence: 99%